2010
DOI: 10.1007/s10096-010-0878-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibiotics resistance and OXA carbapenemases genes in multidrug-resistant Acinetobacter baumannii isolates in central Taiwan

Abstract: This study analyzed the prevalence of antibiotics resistance and the distribution of genes responsible for carbapenems resistance in Acinetobacter baumannii isolates. Clinical A. baumannii isolates were cultured, identified, and collected during the period from May 2007 to February 2009. Antibiotics resistance rates of the clinical isolates were analyzed by antimicrobial susceptibility testing. The distribution of carbapenemase alleles were investigated in the multidrug-resistant (MDR) A. baumannii isolates by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 11 publications
0
15
0
1
Order By: Relevance
“…However, a report from another medical center in northern Taiwan revealed that only 3.4% of CRAB isolates harbored the bla OXA-23 -like gene (11). Reports from 2 hospitals in central Taiwan showed a higher occurrence of the bla OXA-23 -like gene (93% and 96%, respectively) (12,13). Meanwhile, the bla OXA-23 -like gene was less common (0% and 1.1%, respectively) in 2 hospitals in southern Taiwan (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, a report from another medical center in northern Taiwan revealed that only 3.4% of CRAB isolates harbored the bla OXA-23 -like gene (11). Reports from 2 hospitals in central Taiwan showed a higher occurrence of the bla OXA-23 -like gene (93% and 96%, respectively) (12,13). Meanwhile, the bla OXA-23 -like gene was less common (0% and 1.1%, respectively) in 2 hospitals in southern Taiwan (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found a large number of isolates positive for the bla OXA-51 gene (84%), and results similar to that were found by Wisplinghoff et al 26 , who observed 86% of isolates positive for the bla OXA-51 gene. In many studies, the species A. baumannii is the most prevalent and associated with HAIs, and it is also the species with the highest rate of resistance to antimicrobials [27][28] . Carbapenem resistance in isolates of Acinetobacter sp.…”
Section: Discussionmentioning
confidence: 99%
“…Among three A. baumannii isolates, A. baumannii W2 exhibited resistance to all the representative antibiotics including Meropenem, except Tetracycline ( Figure 1a and Table 2). [8,15,[32][33][34]. Yang [8] attributed the resistance to β-lactams as a result including the production of β-lactamases, changes in penicillin-binding proteins that prevent activities of β-lactam drugs, alterations of porin proteins that result in decreased permeability to antibiotics, and the activity of efflux pumps that decreases the concentration of antibiotics within the bacteria.…”
Section: Colony Characteristicsmentioning
confidence: 99%
“…[8,15,[32][33][34]. Yang [8] attributed the resistance to β-lactams as a result including the production of β-lactamases, changes in penicillin-binding proteins that prevent activities of β-lactam drugs, alterations of porin proteins that result in decreased permeability to antibiotics, and the activity of efflux pumps that decreases the concentration of antibiotics within the bacteria. Previous studies have shown that a wide range of extended spectrum betalactamases could be found in A. baumannii clinical isolates [9].…”
Section: Colony Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation